HUBUNGAN ANTARA KECERDASAN NATURALIS DENGAN PERILAKU TANGGUNG JAWAB LINGKUNGAN SISWA - Nina Wirdianti; Ratna Komala; Mieke Miarsyah (Jurnal Biotek, 2020)
Naturalist intelligence is a person's ability to use, understand and classify flora, fauna and nature, along with their interactions, which are then used in solving environmental problems. Naturalist intelligence is one of the predictors relating to responsibility environmental behavior which is one of the efforts to solve environmental problems. This study aims to analyze the relationship between naturalist intelligence and the responsibility environmental behavior of students of SMP Negeri 51 Bandung. The number of respondents consisted of 220 students. The method used in this study is quantitative research with a correlational method. Naturalist intelligence data collection and responsibility environmental behavior using non-test instruments. Analysis of research data using a regression model test (α = 0.05) and correlation coefficient test with Pearson Product Moment test (α = 0.05). The results of the analysis show that there was a positive relationship between naturalist intelligence and responsibility environmental behavior students'.